Jamāʻat Karkūk (The Kirkuk Group): Avant-Garde Pioneers of the Modern Iraqi Prose Poem Descriptive Study - Hamdan , Faraj (Mesopotamian Journal of Arabic Language Studies, 2025)
Since the 1960s, Iraqi prose poetry has vied with both Arabic free verse and traditional verse for literary prominence, evolving amid turbulent political and social transformations. These conditions fostered distinct poetic generations and intensified the interplay between poetry and politics, often producing cultural and aesthetic tensions. Within this milieu, two major trends emerged: a conservative experimental trend extending the project of free verse pioneers, and an avant-garde trend defined by radical experimentation and rebellion against classical and modernist norms alike. At the forefront of the latter stood the Kirkuk Group, whose members — emerging from the city’s unique multilingual and multicultural environment — synthesized Arabic heritage, Sufi poetics, and Western avant-garde influences. Their works combined prose poetry, open-text structures, and intertextual experimentation, challenging conventions while reflecting existential, social, and political realities. The study explores their aesthetic innovations, narrative-prosaic integration, and defiance of state-sanctioned aesthetics, as well as the political marginalization that exiled many of them under the Baʻthist regime yet expanded their transnational influence. Through examining figures such as Fāḍil al-ʻAzzāwī and Sarkūn Būluṣ, this paper argues that the Kirkuk Group’s legacy redefined modern Iraqi poetry, asserting artistic autonomy and marking a decisive stage in the evolution of modern Arabic poetics.